2018
DOI: 10.1007/s12602-017-9378-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Compound Probiotics Ameliorates HFD-Induced Gut Microbe Dysbiosis and Chronic Metabolic Inflammation via the G Protein-Coupled Receptor 43 in Non-alcoholic Fatty Liver Disease Rats

Abstract: The aim of this study was to investigate how the effects of compound probiotics modulate the gut microbiota, short-chain fatty acid (SCFA), body composition, serum and liver lipids, and inflammatory markers in non-alcoholic fatty liver disease (NAFLD) rats. Twenty-four male SD rats were randomly divided into 3 groups: normal control group (standard feed), high-fat diet (HFD) feeding group (83% standard feed + 10% lard oil + 1.5% cholesterol + 0.5% cholate + 5% sucrose), and compound probiotics intervention gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 50 publications
7
64
0
Order By: Relevance
“…Verrucomicrobia was reported to improve glucose metabolism in mice 26 , and recent systematic reviews found adults with obesity and T2DM had fewer Verrucomicrobia than healthy individuals 27,28 . In contrast, another study observed that the proportion of Verrucomicrobia increased in the HFD group 29,30 , which agrees with our results. Furthermore, Tang et al 31 found that Verrucomicrobia was positively correlated with cholic acid, which signi cantly increased in male rats in the NAFLD model.…”
Section: Discussionsupporting
confidence: 92%
“…Verrucomicrobia was reported to improve glucose metabolism in mice 26 , and recent systematic reviews found adults with obesity and T2DM had fewer Verrucomicrobia than healthy individuals 27,28 . In contrast, another study observed that the proportion of Verrucomicrobia increased in the HFD group 29,30 , which agrees with our results. Furthermore, Tang et al 31 found that Verrucomicrobia was positively correlated with cholic acid, which signi cantly increased in male rats in the NAFLD model.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike other SCFAs, the role of valeric acid in gut health is not fully understood. In a limited number of studies, it was found that valeric acid can stimulate the growth of intestinal epithelium and have a beneficial effect on the pathogenesis of diseases such as colitis, cardio-metabolic diseases and cancer (Table 4) [79][80][81]. Table 4.…”
Section: Pparγ (Peroxisome Proliferator-activated Receptor Gamma)mentioning
confidence: 99%
“…The gut microbiota composition is altered in many disease states, such as cardiovascular disease, cancer, malignancy, type 2 diabetes mellitus, obesity, colitis, asthma, psychiatric disorders, inflammatory disorders, disorders of the gut-brain axis, and numerous immune disorders [ 15 , 40 , 41 , 46 48 ]. Modulation of the gut microbiota facilitates a number of health problems; probiotic feeding with a high-fat diet showed alteration of the gut microbiota composition with a decrease in the gram-positive bacteria phyla Firmicutes and Actinobacteria in mice [ 49 ]. In contrast, in a mouse model of hyperlipidemia, the probiotic administration of Lactobacillus led to significant changes in the microbiota composition, including an increased abundance of Bacteroidetes and Verrucomicrobia and a reduced ratio of Firmicutes [ 50 ].…”
Section: Modulation Of Gut Microbiota and Probiotic Speciesmentioning
confidence: 99%